Analisis Laporan Keuangan sebagai Alat untuk Menilai Kinerja Keuangan Perusahaan pada PT Garudafood Putra Putri Jaya Tbk Periode 2021–2025 - Anggita Aulia Khairunissa; Dalizanolo Hulu (CV. Lenggogeni Data Publishing, 2026)
This study aims to analyze the financial performance of PT Garudafood Putra Putri Jaya Tbk for the period 2021–2025 using a quantitative descriptive method based on secondary data from the company's published financial statements on the Indonesia Stock Exchange (IDX). The analysis covers liquidity ratios (Current Ratio, Quick Ratio, Cash Ratio), profitability ratios (GPM, NPM, ROA, ROE), and capital structure and solvency ratios (DER, DAR, LTDER, TIE) following Subramanyam's (2014) framework. The results show that liquidity fluctuated throughout the period, profitability ratios improved consistently since 2022 despite remaining below industry standards, and solvency ratios demonstrated significant structural improvement with declining debt ratios and a rising Times Interest Earned. Overall, the company's financial performance showed a positive trajectory, though short-term liquidity management requires further optimization, making these findings valuable as a reference for investors and stakeholders in investment decision-making and management performance evaluation.